Pesan Moral Dalam Drama Page Turner (Analisis Semiotika Model Charles Sanders Peirce) - Della Cahyaningrum, Della; Syarah, Maya May; Susilowati, Susilowati (Brand Communication, 2024)
Korean drama or often called K-Drama (Korean Drama) is a South Korean cultural product that is popular in various parts of the world, such as in Indonesia. Korean dramas have a great opportunity to convey messages through long storylines in each episode. The Page Turner drama tells the story of someone who almost gave up in facing the challenges of his life, but still struggled through every obstacle to achieve his dreams despite his limitations. The purpose of this study is to determine the moral message contained in the Page Turner drama based on Charles Sanders Peirce's semiotic analysis. The results of the research that the author has done, it can be concluded that the author gets 6 moral messages in the Page Turner drama, including the importance of not being arrogant, the importance of parental support, the importance of caring and never giving up, the importance of honest and open communication, the courage to get back up, and finding new meaning in life